An Investigation Of Roof Garden Design Criteria: Zorlu Center, Kanyon And Hilton Hotel Cases - Kurt, Selva Köroğlu; Canpolat, Bahar Güven (BBDS - Black Book: Drawing and Sketching, 2023)
With the effects inflicted by irregular development and growth of built environment that started to form towards the end of the 20th century, green areas started to lose their original function and started to decrease. Higher cost of land in urban areas have led to a re-evaluation of the usable space on building roofs. Accordingly, the number of design applications the roof sections of terraces and living roof gardens has dramatically increased. This study aimed to investigate the components of a successful roof garden design. Accordingly, the roof garden design criteria were examined under three main titles of climatic, structural, and vegetal. The prestigious Zorlu Center, Kanyon, and Hilton Hotel projects, which are located close to each other in Istanbul, were chosen as the study areas. The areas were investigated by means of on-site discovery, observation, photography and video recording methods. As a result of the study, there were no serious issues regarding the use of climatic and vegetal elements, but there were some inadequacies in the design of structural elements, and furthermore, the structural element designs of the Hilton hotel were more inadequate compared to the other two projects.